The Effect of Sphere of Influence and Economic Distance on the Commodity Composition of Trade in Manufactures - Roemer, John E. (The Review of Economics and Statistics, 1977)
John E. Roemer, The Effect of Sphere of Influence and Economic Distance on the Commodity Composition of Trade in Manufactures, The Review of Economics and Statistics, Vol. 59, No. 3 (Aug., 1977), pp. 318-327